Computer literacy as a condition for the formation of future specialists in education - Larisa Gennadievna Zvereva; Irina Alexeevna Pogodina (Вестник Майкопского государственного технологического университета)
At present information technologies are rapidly developing all over the world, so a man of today should be engaged in self-education and self-improvement. Due to the rapid society informatization and learning conditions during a pandemic, there is an increasing need to improve the computer literacy of current and future teachers, as a computer is the main device in the work of a teacher and in teaching a student in the modern world. In this regard, the formation of computer literacy among students of pedagogical universities and teachers in the current learning environment is an urgent problem in modern society. In accordance with the problem, the main goal of the article is to analyze the works of both domestic and foreign scientists, devoted to the problems of training future teachers in the context of society informatization and the pandemic. For a more detailed analysis and study of the problem of computer literacy formation, the article uses a theoretical research method, which is implemented in considering the fundamental definitions of computer literacy, in highlighting the main levels of computer literacy. The result of the analysis is a listing and description of the basic skills that a pedagogical university student and an employee in the field of education must possess to work with computer information, as well as the use of computer programs in the professional activity of a teacher in the pandemic. Thus, increasing computer literacy is an integral process in the information society, especially during the period of active use of distance learning technologies.